The Abstract Book of the XVIII Conference for Junior Scientists in Psychology - Kvedaraitė, Monika; Dumarkaitė, Austėja (Vilnius University Proceedings, 2021)
Conference for Junior Scientists in Psychology is an annual event, organized by PhD students of Vilnius University, Institute of Psychology. The conference gives a platform for psychology students and junior researchers to present their scientific work and findings.